Transparent patch antenna design using aluminium-doped zinc oxide (ZnO:A1) / Mohd Shahar Mohd Saad - Mohd Saad, Mohd Shahar (2014)
This thesis present the design and simulation of a transparent antenna using Aluminium-doped Zinc Oxide (ZnO:Al) or AZO as a radiating component and glass as a substrate and an Aluminium-doped Zinc Oxide as a ground attached to the substrate. The simulation using Computer Simulation Tools (CST) Microwave Environment software at 1.0 - 3.0 GHZ based on a simple micro-strip patch design. The patch is calculated to get the resonance frequency of 2.4 GHz for WLAN application. The low resistivity value of AZO (1.44x10-4 fi-cm) when converted to conductivity value, a = 6.9444 x 105 S/m will be used in CST Microwave for simulation.